THE WRITTEN DISCOURSE OF INTERVIEWING STYLE FOR A MAGAZINE INTERVIEW - Barrot, Jessie (Universitas Pendidikan Indonesia, 2012)
Abstract: This paper examines the written discourse of interviewing style for the purpose of print publication. Specifically, this paper sought to describe and explain the phases of interviewing procedures, the typology of the questions, and the transitional strategies executed by Oprah Winfrey during her interviews for O Magazine. One hundred and ten (110) response-soliciting statements were subjected to discourse analytic procedure to determine the features of such utterances. The results showed that her interview procedure follows a certain pattern that contributes to her ability to maintain the intimacy, familiarity, and dynamics of conversation. Further, results revealed that the interviewer employs a variety of response-soliciting strategies and transitional strategies that unconsciously put the control and authority in the conversation to the interviewees. Finally, some pedagogical implications were also presented for classroom use. Keywords: discourse analysis, interviewing style, interview questions, written discourse